Legendary star-lord (2014), volume 2 ebook Out of orbit. - Humphries, Sam (Legendary Star-Lord (2014), 2016)
Collects Star-Lord (2015) #6-8; Avengers (1963) #28, 51, 174. Star-Lord and Star-Lady, sitting in a tree — no more! That's right, the engagement of the galaxy is over! But Peter Quill and Kitty Pryde still have to share a ship...and work...and friends...and…yeesh. This is going to get awkward! Fortunately, they're surrounded by caring, communicative teammates like…Drax…and Groot…and Rocket…hoo boy. But when their legendary breakup captures the Collector's imagination, can Peter and Kitty put aside their differences and make it out of his clutches alive? It's a cosmic conundrum that could make their split seem like a honeymoon! Plus: The Collector takes on the Avengers in three classic tales! Author: Sam Humphries. Illustrator: Javier Garron. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com